Is Chinese Democracy democracy? - TAN, Sor-hoon (Institutional Knowledge at Singapore Management University, 2022)
Part of a series of responses to Jean-Paul Gagnon’s democracy ‘Science of Democracy’ project, this post explores the challenge that ‘Chinese democracy’ represents for that project, and argues that exploring the Chinese case helps us establish the wide-ranging parameters to the project. It also identifies the theoretical issues we must confront for the project to succeed.